1999
DOI: 10.1089/152581699319821
|View full text |Cite
|
Sign up to set email alerts
|

The Alterations of the Activities of Coagulation Inhibitors and Fibrinolytic Factors in Stored Cord Blood Could Affect the Yield of Progenitor Cells During Processing

Abstract: We assessed the changes in the activities of hemostatic variables by the storage temperature and time interval between collection and separation of cord blood (CB) and analyzed their relationship with the yield of progenitor cells during processing. Total nucleated cell (TNC) and CD34+ cell counts were significantly higher in the CB stored at ambient temperature than at 4 degrees C. The significant loss of TNC and CD34+ cells continued to 24 h after collection in CB stored at 4 degrees C, but loss of TNC began… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Initially, the flasks were slowly agitated, but this led to significant clumping of the white cells at 4°C, so the agitation was omitted. 20 No significant differences in recovery of clonogenic cells were found between agitation and no agitation at 22°C (data not shown). Samples of 100 ml were stored at 22°C in Lifecell PL732 Culture Bags (Nexell Therapeutics Inc, Irvine, CA, USA).…”
Section: Storage Conditionsmentioning
confidence: 87%
“…Initially, the flasks were slowly agitated, but this led to significant clumping of the white cells at 4°C, so the agitation was omitted. 20 No significant differences in recovery of clonogenic cells were found between agitation and no agitation at 22°C (data not shown). Samples of 100 ml were stored at 22°C in Lifecell PL732 Culture Bags (Nexell Therapeutics Inc, Irvine, CA, USA).…”
Section: Storage Conditionsmentioning
confidence: 87%
“…In a previous study [12], we observed small clumps in the CB following red cell depletion, particularly in the samples stored longer than 24 hr. Microscopic findings of small clumps revealed aggregates of nucleated cells consisted of progenitor cells admixed with fibrin strands.…”
Section: Introductionmentioning
confidence: 57%
“…This phenomenon was related to the alterations of the activities of coagulation inhibitors and fibrinolytic factors in elapsed CB. In particular, the plasma activity of ␣ 2 antiplasmin, which is the most important fast-reacting plasmin inhibitor, decreased significantly in CB stored at ambient temperature for 48 hr [12].…”
Section: Discussionmentioning
confidence: 96%
“…Most UCB banks collect UCB between Sunday and Friday to allow processing of the unit within 24 h, and a prolongation of the working period of the laboratory would significantly increase personnel costs [21]. Storage of UCB longer than 24 h would decrease the yield of nucleated cells and CD34+ cells [22]. The consent procedure at our institution usually takes place during the routine outpatient pregnancy visits around 4 weeks before the estimated date of delivery or when the patient in labor is pain-free due to an epidural anesthesia in the 1st stage of labor.…”
Section: Discussionmentioning
confidence: 99%